Reef‐wide evidence that the presence of sharks modifies behaviors of teleost mesopredators. Issue 2 (2nd February 2021) - Lester, E. K.; Langlois, T. J.; Simpson, S. D.; McCormick, M. I.; Meekan, M. G.
Abstract: The idea that the presence of sharks impacts the behavior of mesopredatory reef fishes is controversial and lacks clear evidence at reef‐wide scales. We compared the abundance and behavior of these reef fishes in response to the presence of reef sharks using Baited Remote Underwater Video System (BRUVS) deployments in two adjacent reef systems where sharks have either been exclusively targeted by fishing or protected by a no‐take marine reserve. For a subset of videos, we also compared the behavior of mesopredatory reef fishes immediately before and after the appearance of sharks in the video. On reefs where sharks were more abundant, mesopredatory fishes spent less time swimming in midwater (i.e., away from shelter) and guarding bait compared to reefs where sharks have been selectively removed. The same responses occurred after the appearance of sharks in the video. Reactions to sharks varied both in strength and type among species of mesopredator and were mediated by the availability of shelter on the reef and, for one species, by the levels of activity of the reef sharks. In contrast, we did not find that the presence of sharks influenced the abundance of mesopredators at either reef system across hour‐long videos or immediately before and after a shark appeared in the video. Collectively, our findings show that the presence of sharks reduces the propensity of mesopredatory fish to engage in potentially risk‐prone behaviors over large spatial scales and that these interactions are mediated by the behavioral characteristics of both predators and prey, and the environment in which they co‐occur. Our results are consistent with the idea that sharks as predators or larger competitors initiate changes in the behavior of mesopredatory reef fishes likely to affect trophic structuring within coral reef ecosystems.